The role of informational, normative, and avoidance identity styles in prediction of social anxiety in medical science students - Farideh Daneshniya; Sharareh Zarabi; Zahra Karimiyan (Gonabad University of Medical Sciences, 2018)
Social anxiety is a psychological disorder affected by cognitive aspects of person. The aim of study was to investigate the role of informational, normative, and avoidance identity styles in predicting the variance of social anxiety amongst Iranian medical science students. Using stratified sampling method, one hundred and twenty students were selected from each of the colleges of medicine, pharmacy, nursing, and public health. Berzonsky identity style questionnaire, and Liebowitz et al social anxiety test were used for data collection. According to obtained results informational, normative, and avoidance identity styles can predict the variance of social anxiety. Moreover, there was a significant and negative correlation between social anxiety and informational style and normative identity style; Meanwhile, there was a positive significant correlation between social anxiety and avoidant identity style. With respect to findings of current study, providing more opportunities in the colleges and faculty is recommended in order to improve informational and normative identity styles among students, and reduce social anxiety consequences.